Unity and diversity in grammaticalization scenarios - Malchukov, Andrej; Bisang, Walter (Studies in Diversity Linguistics, 2017)
The volume contains a selection of papers originally presented at the symposium on "Areal patterns of grammaticalization and cross-linguistic variation in grammaticalization scenarios" held on 12-14 March 2015 at Johannes Gutenberg University of Mainz. The papers, written by leading scholars combining expertise in historical linguistics and grammaticalization research, study variation in grammaticalization scenarios in a variety of language families (Slavic, Indo-Aryan, Tibeto-Burman, Bantu, Mande, "Khoisan", Siouan, and Mayan). The volume stands out in the vast literature on grammaticalization by focusing on variation in grammaticalization scenarios and areal patterns in grammaticalization. Apart from documenting new grammaticalization paths, the volume makes a methodological contribution as it addresses an important question of how to reconcile universal outcomes of grammaticalization processes with the fact that the input to these processes is language-specific and construction-specific.